Effect of Replacement of Maize with Dry Bakery Waste in Broiler Diet - Epao; Ramteke, BN; Gadegaonkar, GM (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
An experiment was conducted on 240 day-old broiler chicks for a period of six weeks in which the chicks were randomly divided into four equal groups viz Control (C), T1, T2 and T3 comprising of 60 birds each with three replicates of 20 birds in each group.The birds from group C received Corn Soybean meal based diet, the birds from group T1, T2 and T3 received diet in which maize was replaced with dry bakery waste (DBW) at 20, 40 and 60% level, respectively. The final live body weight, total gain in weight, feed consumption, feed conversion ratio, average dressing percentage, giblet weight, serum albumin, globulin, cholesterol, triglycerides, LDL and VLDL values for group C, T1, T2 and T3were comparable, however, average serum HDL values were significantly lower in T1 and T2 than Control. Highest net profit per kg of bird were recorded in Group T3 .